Manufacturing of aluminum mirrors for cryogenic applications - Kinast, Jan; Schlegel, Ralph; Kleinbauer, Knut; Steinkopf, Ralf; Follert, Roman; Dorn, Reinhold J.; Lizon, Jean Louis; Hatzes, Artie; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
Several mirrors for the upgrade of the CRyogenic high-resulution InfraRed Echelle Sprectrograph (CRIRES) at the Very Large Telescope, were manufactured by diamond turning and polishing. These mirrors will be used in the crossdispersion unit (CDU) and the fore optics of the instrument. For background level reasons, the operational temperature of the CDU is set to 65 K. Therefore, the flat and spherical mirrors used in the CDU, which are made of melt-spun aluminum alloy Al6061, had to be artificially aged, to improve the dimensional stability at cryogenic temperatures. After diamond turning, magnetorheological finishing (MRF) was used for a deterministic shape correction and to remove the turning marks of the RSA6061 mirrors. To reduce the micro-roughness, a further smoothing step was necessary. A micro-roughness between 1 nm RMS and 5 nm RMS as well as shape deviations below 35 nm RMS were achieved. The mirrors were coated by inline magnetron sputtering with a high-reflective gold layer or protected silver, respectively.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Cryogenic; Magnetorheological finishing; Manufacturing; Mirrors; Polishing